Experimental transmission of Tahyna virus (California group) to wild rabbits (Oryctolagus cuniculus) by mosquitoes - Rödl, P; Bárdos, V; Ryba, J (Folia parasitologica, 1979)
Two wild rabbits (Oryctolagus cuniculus) were subcutaneously infected with a dose of 2.6 dex. i.c. LD50/0.02 ml of extraneurally passaged Tahyna virus strain "236". During the 24-72 hours interval p.i. viremia was demonstrated in both animals ranging from 1.0 to 3.42 dex. i.e. LD50/0.02. Mosquitoes Aedes vexans, which had fed on them, transmitted the virus to one of three other rabbits. During 24-96 hours interval after terminated feeding of infectious mosquitoes viremia was detected in this animal ranging from 0.49 to 4.08 dex i.c. LD50/0.02 ml. Seroconversion was revealed by means of plaque reduction neutralization test 11 days after infection.
Keywords: Encephalitis, California; Encephalitis, Arbovirus; Female; králíci; kalifornská encefalitida; Antibodies, Viral; hmyz - vektory; encefalitida přenášená členovci; mužské pohlaví; Insect Vectors; zvířata; ženské pohlaví; Rabbits; Animals; protilátky virové; Male; viry kalifornské encefalitidy; Culicidae; Encephalitis Virus, California